Integrating Uzbek Folk Tales into the Primary School Curriculum for Patriotism and Friendship Education (Eurasian Research Bulletin, 2023)
This article employs a mixed-methods approach, combining qualitative data from interviews with educators and quantitative data from surveys administered to students. The findings highlight the significance of cultural heritage in education and the power of folk tales as educational resources. Uzbek folk tales are recognized for their ability to convey moral lessons, instill values, and engage students' imagination. Also, this article contributes to the understanding of how the integration of Uzbek folk tales can enhance patriotism and friendship education in primary schools. It provides insights for educators, policymakers, and curriculum developers to effectively incorporate cultural heritage into the curriculum, foster a sense of cultural identity, and nurture positive values and relationships among students.